ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PREVALENSI STUNTING, TINGKAT PENGANGGURAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI NEGARA ASIA TENGGARA - Ningsih, Sekar Ayu; Ekaputri, Retno Agustina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p03, 2024)
Human Development Index as a parameter utilized in measuring to what extent a country is able to access the results of development produced in various aspects, such as health, income, education or others. This study will focus in analyzing the influence of economic growth, prevalence of stunting, unemployment rate on HDI in Shoutheast Asia in 2001 to 2022 whether it has a positive or non-positive relationship direction, because there are striking differences in HDI in Southeast Asia with other regions, such as Europe. The method in this study was carried out using panel data regression. The data used for the independent variables are economic growth, prevalence of stunting, and unemployment rate, then the data used as the dependent variable is HDI. The results show that economic growth, prevalence of stunting, and unemployment rate have an influence on the Human Development Index in Southeast Asian countries together. In addition, in the t-test, it was found that each variable, namely economic growth, prevalence of stunting and unemployment rate, has an non positive influence on HDI in Southeast Asian countries. So that later this research can help governments in Southeast Asian countries in making more appropriate policies.